A negative electrode colloidal solution, a preparation method thereof, a negative electrode sheet, and a lithium ion battery

By using isopropanol, ethylene carbonate, and polyether dimethylfluorosiloxane as surface tension leveling agents in lithium battery electrode gel, the problems of edge lifting and cracking during electrode coating are solved, the peel strength of the electrode and the commercial value of the battery are improved, the production process is simplified, and the environmental pollution risk is reduced.

CN120727827BActive Publication Date: 2025-11-18UNION LITHPLUS ENERGY (LIAONING) CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511170972.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-21
Publication Date
2025-11-18
Estimated Expiration
2045-08-21

AI Technical Summary

Technical Problem

Existing lithium battery electrodes are prone to edge lifting and cracking during the coating process, resulting in low peel strength and increasing the risk of low capacitance and short circuits. At the same time, existing improvement methods may cause environmental pollution or increase the number of processes and reduce production efficiency.

Method used

Isopropanol, ethylene carbonate, and polyether dimethylfluorosiloxane are used as surface tension leveling agents. By adjusting the wettability and leveling properties of the electrode gel, the uniform distribution of the electrode is improved, the warping and cracking are reduced, and the production efficiency is improved by simplifying the preparation process.

Benefits of technology

This achieves uniform coating and high peel strength of the electrode sheets, reduces the risk of low capacity and short circuit in lithium batteries, maintains the environmental performance and production efficiency of the batteries, and enhances the commercial value of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120727827B_ABST
    Figure CN120727827B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of lithium batteries, in particular to a negative electrode colloidal solution, a preparation method thereof, a negative electrode sheet and a lithium ion battery. The negative electrode colloidal solution comprises a negative electrode main material, wherein the negative electrode main material comprises 3500 parts of a negative electrode active material and 36-60 parts of a surface tension leveling agent, and the surface tension leveling agent is at least two of isopropyl alcohol, ethylene carbonate and polyether dimethyl fluorosiloxane. The negative electrode colloidal solution can improve the problems of edge curling and cracking of the electrode sheet, so that the lithium battery cell has stable electrical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium battery technology, and in particular to a negative electrode gel liquid and its preparation method, a negative electrode sheet, and a lithium-ion battery. Background Technology

[0002] Since the beginning of the 21st century, lithium battery technology has developed rapidly, enabling lithium-ion batteries to possess high energy density, support fast charging, and excellent cycle life. More and more handheld power tools, electronic communication products, and other devices are beginning to use lithium-ion batteries and their polymer batteries. Meanwhile, 3C digital products, which were among the first to use lithium batteries, have successively developed various lithium-ion materials, with high-energy-density materials being particularly favored. This is because higher energy density means a smaller size and longer battery life. However, as electronic products become increasingly smaller, increasing the thickness of the active material in the electrode is no longer suitable for increasing energy density. Thicker electrodes make subsequent assembly more difficult; for example, during electrode drying, problems such as edge warping, cracking, and difficulty in adhesion can easily occur, increasing the difficulty of the subsequent winding process. Lower peel strength of the negative electrode makes it easier for material to fall off, increasing the risk of low capacity or even short circuits in the lithium battery. Therefore, producing electrodes with uniform areal density and flawless appearance has become a major challenge in the industry.

[0003] To obtain lithium batteries with stable lifespans, the first step is to manufacture better electrodes. Currently, there are two main process approaches. One is to improve coating technology, which is achieved by optimizing the drying temperature during coating and setting up a stepped drying process. The second is to optimize the preparation method of the raw material gel solution. By adding wetting agents, leveling agents, and changing the polarity of the materials, the gel solution can be evenly distributed on the metal electrode to obtain an electrode with a stable active material layer.

[0004] Current methods for improving electrode cracking and material shedding mainly involve adding N-methylpyrrolidone (NMP), ethylene carbonate (EC), and 1,3-butanediol. For example, Chinese patent application CN114335528A discloses adding N-methylpyrrolidone to the negative electrode gel solution to solve the problem of negative electrode cracking. However, N-methylpyrrolidone is a toxic and harmful organic solvent that can pollute the environment. Another example is Chinese patent application CN119297282A, which discloses an improvement process for coating cracking of aqueous negative electrode sheets in lithium-ion batteries. Adding a small amount of a mixture of isopropanol, propylene glycol, and allyl alcohol can effectively improve the problem of coating cracking in aqueous negative electrode sheets. However, the mentioned preparation method requires first preparing the gel solution and then adding other materials such as the negative electrode active material to the gel solution, which undoubtedly adds a step to lithium battery manufacturing and reduces production efficiency.

[0005] Therefore, it is extremely important to develop a method to improve edge curling and cracking during coating, thereby increasing electrode peel strength and directly reducing the probability of low capacity and short circuit in lithium batteries, without affecting the cycle performance and environmental impact assessment rating of lithium batteries. Summary of the Invention

[0006] To improve the problems of edge lifting and cracking during electrode coating and to ensure a reduction in the low capacity and short circuit probability of lithium batteries, this application provides a negative electrode gel solution, its preparation method, a negative electrode sheet, and a lithium-ion battery.

[0007] In a first aspect, this application provides a negative electrode colloidal liquid, employing the following technical solution:

[0008] The anode material includes, by mass, 3500 parts of anode active material and 36-60 parts of surface tension leveling agent. The surface tension leveling agent is at least two of isopropanol, ethylene carbonate, and polyether dimethyl fluorosiloxane, specifically including 0-65 parts of isopropanol, 0-36 parts of ethylene carbonate, and 0-40 parts of polyether dimethyl fluorosiloxane. If two of the above three substances are not present simultaneously, the total is 0 parts.

[0009] Isopropanol and ethylene carbonate, as surface tension leveling agents, possess advantages such as stability, low boiling point, and minimal residue. Polyether dimethylfluorosiloxane is widely used in slurry dispersion, serving to wet, increase leveling properties, and defoam. Adding the aforementioned surface tension leveling agent to the negative electrode colloidal solution improves its wettability, effectively reducing the surface tension after coating and ensuring uniform distribution of the colloidal solution on the metal foil, thus mitigating electrode edge curling and cracking during drying. Secondly, isopropanol and ethylene carbonate are easily volatile during drying, leaving low residue and eliminating the need to increase oven temperature. Polyether dimethylfluorosiloxane is inexpensive and requires only a small amount, offering a low-cost advantage. Therefore, the surface tension leveling agent not only effectively addresses electrode edge curling and cracking during drying but also leaves no residue. The prepared electrode has uniform surface density and a flawless appearance, resulting in stable electrical performance in the lithium battery cell.

[0010] The mixture of isopropanol and ethylene carbonate helps to improve the edge curling of the electrode, resulting in a smaller diameter of the wound cell and increased energy density. However, attention should be paid to the method of adding the surface tension leveling agent. Improper addition may reduce the peel strength of the electrode, thereby causing low capacitance and short circuits in the cell.

[0011] The surface tension leveling agent is isopropanol, ethylene carbonate, and polyether dimethylfluorosiloxane. Experiments have shown that the negative electrode gel prepared using the above-mentioned surface tension leveling agent is less prone to edge curling during the coating and drying process, thus ensuring the commercial value of the lithium-ion battery.

[0012] The negative electrode active material is one or both of natural graphite and artificially synthesized graphite;

[0013] The conductive agent is at least one of carbon black and conductive graphite;

[0014] The emulsifying modifier is polystyrene-butadiene rubber;

[0015] The adhesive is at least one of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.

[0016] Secondly, this application provides a method for preparing a negative electrode colloidal liquid, which adopts the following technical solution:

[0017] A method for preparing a negative electrode colloidal liquid is as follows: Take the negative electrode active material, conductive agent, binder, and ethylene carbonate, stir, and then add deionized water to deflocculate the powdered material into large clumps. Appropriately increase the stirring speed, gradually add deionized water until the solid content is adjusted to 52%±0.5%, stir at room temperature, add an aqueous solution of isopropanol and polyether dimethylfluorosiloxane, then add an emulsifying regulator, use deionized water to adjust the viscosity to 2000-3000 cP, then vacuum and maintain for at least 40 minutes to defoam, and filter to obtain the negative electrode colloidal liquid.

[0018] In the preparation method described above, the powdered material is fed by direct weighing. Deionized water is added directly to the mixing tank. This simple operation process improves production efficiency and reduces the frequency of cleaning the mixing tank, indirectly lowering production costs.

[0019] A method for preparing a negative electrode colloidal solution, the method is as follows:

[0020] Step 1: Prepare the surface tension leveling agent. Prepare an aqueous solution of polyether dimethyl fluorosiloxane and an aqueous solution of ethylene carbonate. Add the prepared ethylene carbonate aqueous solution to the prepared polyether dimethyl fluorosiloxane aqueous solution to adjust the polarity, changing it from non-polar to polar. Finally, add isopropanol to the solution to prepare the surface tension leveling agent, and keep it for later use.

[0021] Step 2: Mix the negative electrode active material, conductive agent, and binder evenly, add deionized water to break up the powdered material into large clumps, increase the stirring speed, and gradually add deionized water until the solid content is adjusted to 52%±0.5%. Stir at room temperature, then add surface tension leveling agent and emulsifying regulator, and add deionized water to adjust the viscosity to 2000-3000 cP. Vacuum the mixture and keep it for at least 40 minutes to defoam, then filter to obtain the negative electrode colloidal liquid.

[0022] Thirdly, this application provides a negative electrode sheet, which is prepared using the following technical method:

[0023] A negative electrode sheet, wherein the coating of the negative electrode sheet is mainly prepared by coating, drying and rolling of negative electrode active material, binder and conductive agent.

[0024] Fourthly, this application provides a lithium-ion battery, which adopts the following technical solution:

[0025] A lithium-ion battery includes: a positive electrode, a coated separator, an electrolyte, and the aforementioned negative electrode.

[0026] The lithium-ion battery described in this application has excellent electrochemical performance, meets environmental protection requirements, and has broad market prospects. Attached Figure Description

[0027] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments or prior art are briefly introduced below. Obviously, the accompanying drawings in the following description are only some application examples of this application.

[0028] Figure 1 Line graphs showing the peel strength data of the negative electrode sheets prepared in Examples 1 and 2.

[0029] Figure 2 Comparison chart of contact angle and surface tension variance analysis in the orthogonal experiment described in Example 3.

[0030] Figure 3 Viscosity change of the negative electrode colloidal liquid in the orthogonal experiment described in Example 3 over 24 hours.

[0031] Figure 4 State diagrams of the negative electrode colloidal liquids obtained in Example 5 and the comparative example, where A is the negative electrode colloidal liquid obtained in Example 5 and B is the negative electrode colloidal liquid obtained in the comparative example.

[0032] Figure 5 The electrode images after the negative electrode colloidal liquid coating described in the comparative example are shown in A and B, which are electrode state images at different angles.

[0033] Figure 6 The electrode image obtained in Example 5 after coating with the negative electrode gel is shown. A and B are electrode state images at different angles. Detailed Implementation

[0034] To make the technical problems, solutions, and beneficial effects of this application clearer, the following detailed description is provided with reference to application examples. The application examples described herein are merely a representative part of the invention, and not all application cases. It should be understood that the specific application examples described herein are only for explaining this application and are not intended to limit this application.

[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of the invention.

[0036] The terms "include" and "contain" as used in this article cover both cases where only the mentioned elements exist and cases where other unmentioned elements exist in addition to the mentioned elements.

[0037] All solvents and reagents involved in this invention are of analytical purity or better.

[0038] All water used in this invention, including deionized water, conforms to Grade III water as defined in GB / T6682-2008.

[0039] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. Unless otherwise stated, the singular forms "a," "the," and "the" used also refer to the plural forms.

[0040] Example 1

[0041] 1. Preparation of negative electrode colloidal solution

[0042] The negative electrode colloidal solution is prepared using the following steps:

[0043] Weigh out 3500g of graphite anode active material and 35g of carbon black conductive agent according to the formula requirements, add 39.4g of sodium carboxymethyl cellulose binder (accurate to 0.1g), and then weigh out 28g of ethylene carbonate. Add the above powdered materials to a mixing tank, and then stir at 10 rpm for 5 to 15 minutes to ensure the materials are evenly mixed. Add 1900g of deionized water to break up the powdered material into large clumps (note that if the material does not form large clumps, add more deionized water as needed). Increase the stirring speed appropriately to 15 rpm, while maintaining the angular velocity of the stirring paddle to ensure sufficient shear force to disperse the materials. Next, deionized water was gradually added to the mixing tank until the solid content was adjusted to 52% ± 0.5%. The mixture was stirred for 2 hours at a revolution speed of 25 rpm at room temperature, with the dispersion speed set 100 times higher. The material on the agitator was scraped off, and then a surface tension leveling agent was added, namely a solution obtained by dissolving 9.45 g of isopropanol and 11.55 g of polyether dimethyl fluorosiloxane in 92.2 g of deionized water. 145.9 g of polystyrene-butadiene rubber (PSB) was added to the mixing tank as an emulsifier. The viscosity was adjusted using deionized water, with a viscosity between 2000 and 3000 cP being suitable. The mixing tank was then evacuated and maintained for at least 40 minutes to defoam. Finally, the mixture was filtered through a 200-mesh standard sieve to obtain the negative electrode colloidal solution.

[0044] 2. Preparation of negative electrode sheet

[0045] The above-mentioned negative electrode colloidal liquid is coated on copper foil after passing through a 150-mesh (or finer) standard sieve. After drying, rolling, and slitting, the negative electrode sheet is obtained.

[0046] Example 2

[0047] 1. Preparation of negative electrode colloidal solution

[0048] The negative electrode colloidal solution is prepared using the following steps:

[0049] Weigh 3500g of graphite anode active material and 35g of carbon black conductive agent according to the formula requirements, and add 39.4g of sodium carboxymethyl cellulose binder, accurate to 0.1g. Weigh 25g of polyether dimethyl fluorosiloxane to prepare an aqueous solution. Weigh 20g of ethylene carbonate to prepare an aqueous solution. Add the prepared ethylene carbonate aqueous solution to the prepared polyether dimethyl fluorosiloxane aqueous solution to adjust the polarity, changing it from non-polar to polar. Finally, add 20g of isopropanol to this solution to prepare a surface tension leveling agent, and reserve it for later use. Put the powdered materials into a mixing tank, and then set the stirring speed to 10 rpm for 5 to 15 minutes to mix the materials evenly. Then add 1900g of deionized water to dissolve the powdered materials into large clumps (note that if the materials do not form large clumps, add more deionized water as needed). Appropriately increase the stirring speed to 15 rpm, while maintaining the angular velocity of the stirring paddle to ensure sufficient shear force to disperse the materials. Next, deionized water was gradually added to the mixing tank until the solid content was adjusted to 52% ± 0.5%. The mixture was stirred for 2 hours at a revolution speed of 25 rpm at room temperature, with the dispersion speed set 100 times that revolution speed. The material on the agitator was scraped off, and then the prepared surface tension leveling agent was added. 145.9 g of emulsifying agent, polystyrene-butadiene rubber, was added to the mixing tank. Deionized water was used to adjust the viscosity; a viscosity of 2000 to 3000 cP was suitable. The mixing tank was then evacuated and maintained for at least 40 minutes to defoam. Finally, the mixture was filtered through a 200-mesh standard sieve to obtain the negative electrode colloidal solution.

[0050] 2. Preparation of negative electrode sheet

[0051] The above-mentioned negative electrode colloidal liquid is coated on copper foil after passing through a 150-mesh (or finer) standard sieve. After drying, rolling, and slitting, the negative electrode sheet is obtained.

[0052] Example 3: Comparison of peel strength of negative electrode sheets prepared by different methods

[0053] Electrode 90° peel strength test

[0054] The 90° peel strength of the electrode was tested according to the method described in GB / T2792-2014. The peel strength of the negative electrode prepared in Example 1 and Example 2 was tested, as shown in Table 1.

[0055] Table 1. Peel strength data of the negative electrode sheets prepared in Examples 1 and 2

[0056]

[0057] Draw a data line graph based on Table 1. Figure 1 .

[0058] See Figure 1Therefore, it can be seen that, among the two methods of adding surface tension leveling agents described in Examples 1 and 2, the negative electrode sheet prepared by the addition method in Example 2 has a significantly higher peel strength than the negative electrode sheet prepared in Example 1. Higher peel strength of the negative electrode sheet reduces the difficulty of subsequent winding processes, results in higher energy density, and makes it less prone to electrode sheet loss when the coating thickens. This reduces the risk of low capacity or even short circuits in lithium batteries.

[0059] Example 4

[0060] I. Preparation of Lithium-ion Batteries

[0061] 1. The negative electrode sheet obtained in Example 2

[0062] 2. Preparation of the positive electrode sheet

[0063] Accurately weigh 98.2% (w / w) of lithium nickel cobalt manganese oxide cathode material, 1% (w / w) of PVDF binder, 0.55% (w / w) of LD435 conductive agent, and 0.2% (w / w) of polyvinylpyrrolidone dispersant. Then, premix the above powder materials in a mixing tank. After 10 minutes, add N-methylpyrrolidone and stir to obtain a semi-solid material. Then, add 0.05% (w / w) of single-walled carbon nanotubes, and continue stirring with appropriate amounts of N-methylpyrrolidone. Control the viscosity between 4000 and 8000 cP. Then, pass the cathode gel solution through a 200-mesh standard sieve and coat it onto aluminum foil. After drying, rolling, and slitting, obtain the cathode sheet.

[0064] 3. Preparation of the diaphragm

[0065] Using a 5μm polyethylene membrane as the base membrane, a coating layer is coated on the two opposite surfaces of the base membrane. The coating layer consists of a 2μm thick alumina ceramic layer close to the base membrane and a 1μm thick PVDF adhesive layer coated on the ceramic layer, to obtain a composite membrane with a thickness of 8μm.

[0066] 4. Preparation of electrolyte

[0067] 30.0 g of ethylene carbonate, 30.0 g of propylene carbonate and 30.0 g of propyl propionate were mixed evenly in an environment with a moisture content of 0.1 ppm to obtain an organic solvent; 13.23 g of 1 mol / L lithium hexafluorophosphate was added to the organic solvent and stirred until completely dissolved; then 5.16 g of fluoroethylene carbonate was added and stirred evenly to obtain an electrolyte.

[0068] 5. Preparation of lithium-ion batteries

[0069] The above-mentioned negative electrode sheet, positive electrode sheet and composite separator are used to obtain the core by winding. After the core is put into the shell, the above-mentioned electrolyte is injected. Then, the lithium-ion battery is obtained by welding the bottom cap, sealing, formation and capacity testing.

[0070] Based on the exploration and results of previous experiments, an orthogonal experiment was designed. Taking the preparation method of Example 2 as the experimental basis, different proportions of surface tension leveling agent were used as orthogonal examples to design an L8(23) orthogonal experiment. The results of the orthogonal experiment on the addition amount and ratio of surface tension leveling agent are shown in Table 2 below.

[0071] Table 2. Orthogonal experimental table of addition ratio of each component of surface tension leveling agent

[0072]

[0073] The above orthogonal experiments are just examples of applications with relatively representative data. This article cannot list all the additions of orthogonal cases, so only the orthogonal experimental cases of L8(23) are shown for illustration.

[0074] Table 3 shows the negative electrode colloidal solution and coating surface condition recorded in orthogonal experimental example L8(23).

[0075]

[0076] Analysis of variance was used to study the differences in the effects of contact angle and surface tension of the negative electrode colloidal solution on the surface state of the electrode, and a comparison of the variance analysis results was plotted. Figure 2 .

[0077] See Figure 2 Therefore, it can be seen that orthogonal experiment 4 shows an inflection point trend in the variance of contact angle and surface tension data. It can be determined that when the mass of the surface tension leveling agent is 59g, the surface state of the prepared negative electrode sheet is the best, and the negative electrode gel wets the copper foil with a small contact angle and low surface tension during coating.

[0078] II. Test Methods for Lithium-ion Batteries

[0079] 1. Surface tension leveling agent residue test

[0080] Eight orthogonal experimental groups of coated and dried negative electrode sheets were coated with powder. Then, the residual surface tension leveling agent in the powder was dissolved and extracted with anhydrous ethanol (analytical grade). After sufficient settling, the content of surface tension leveling agent in the supernatant was tested by gas chromatography-mass spectrometry. Standard curves of different concentrations were prepared according to the composition of the surface tension leveling agent. The residual rate of surface tension leveling agent was calculated based on the amount of surface tension leveling agent added.

[0081] 2. Viscosity change of negative electrode colloidal liquid after standing

[0082] Approximately 600g of the negative electrode colloidal solution from each of the eight orthogonal experimental groups was placed in a 1000ml beaker, sealed, and allowed to stand for 24 hours. During this period, the viscosity was measured every 2 hours using a rotational viscometer. The difference between the final viscosity and the initial viscosity is the thixotropic value of the colloidal solution.

[0083] III. Test Results of Lithium-ion Batteries

[0084] Table 4. Viscosity thixotropic value and residual rate of surface tension leveling agent in the negative electrode gel prepared in 8 orthogonal experimental groups.

[0085]

[0086] Referring to Table 4, the test results of the surface tension leveling agent residue rate show that in orthogonal experiments 6-8, a significant amount of surface tension leveling agent residue remained after drying, especially in orthogonal experiments 6 and 7, where the residue rate was extremely high. These residues easily reduce lithium-ion insertion and extraction, affecting the charge and discharge rate of the lithium battery. Lithium batteries with excessively low charge and discharge rates are easily eliminated from the market. In contrast, the surface tension leveling agent in orthogonal experiments 1-4 had a lower boiling point and a residue rate of only 0.8%-1.2%, meaning that the surface tension leveling agent was essentially carried away by the heat of the oven during the drying process of the negative electrode, effectively avoiding the impact of surface tension leveling agent residue on the performance of the lithium-ion battery.

[0087] Combination Figure 3 Analysis of the thixotropic viscosity of the negative electrode colloidal solution reveals that solutions with high thixotropic viscosity tend to exhibit significant viscosity changes under shear force, thus affecting the coating difficulty and leading to uneven coating. In orthogonal experiments 6 and 7, the surface tension leveling agent resulted in extremely high thixotropic viscosity values ​​for the negative electrode colloidal solution, causing substantial viscosity changes over a period of time, which is detrimental to the coating process. Furthermore, Table 1 shows that the electrode sheet in orthogonal experiment 6 also exhibited edge curling. In contrast, the surface tension leveling agent added in orthogonal experiment 4 significantly reduced the thixotropic viscosity of the negative electrode colloidal solution, thereby optimizing the coating process. In other words, the surface tension leveling agent added in orthogonal experiment 4 enabled the negative electrode colloidal solution to maintain a stable flow state with minimal viscosity changes, which is beneficial for producing negative electrode sheets with a good surface condition.

[0088] Example 5

[0089] In this embodiment, the negative electrode colloidal liquid was prepared according to the technical solution of Example 2, and the amount of surface tension leveling agent added in orthogonal experiment 4 was used as the basis for addition.

[0090] Comparative Example

[0091] This comparative example prepared a negative electrode colloidal solution according to the technical solution of Example 5, without adding a surface tension leveling agent. The difference in solid content compared to Example 5 was compensated for by adding deionized water. The final viscosity was adjusted according to the viscosity of the example to control it within ±1500 cP.

[0092] Comparison results

[0093] I. Negative Electrode Colloidal State

[0094] Both Example 5 and the comparative example exhibited good flowability. However, in the comparative example, a small amount of emulsifying agent floated on the surface of the gel-like liquid, resulting in uneven dispersion and a milky-white imprint with blue fluorescence, exhibiting a "blue floating" phenomenon. Figure 4 As shown. Conversely, the negative electrode gel of Example 5 did not exhibit this phenomenon. We know that the main reason for this phenomenon is the poor compatibility between the emulsifier and the binder. The branching effect in the emulsifier and binder changes the polarity to non-polarity, thus becoming hydrophilic, making them easily suspended in water, which in turn reduces the adsorption of the negative electrode active material. This leads to uneven distribution of the negative electrode active material in the negative electrode gel. However, adding a surface tension leveling agent can fully wet the negative electrode active material, making the gel less prone to stratification.

[0095] II. Cyclic Performance Testing

[0096] The lithium-ion battery was subjected to cycle performance testing. The test method was as follows: at 18℃ to 30℃, the voltage range was 2.75 to 4.43V, the rate was 1.3C / 1C, and small current charge and discharge was performed at 0.5C and 0.2C every 50 cycles, for a total of 400 cycles.

[0097] Ten lithium batteries (2500mAh each) were assembled from the formulations of the comparative example and Example 5 to observe the capacity, internal resistance and cycle life of the lithium-ion batteries. The average value of the 10 parallel samples was statistically analyzed, and the specific results are shown in Table 5.

[0098] Table 5 Performance of lithium-ion batteries prepared from the negative electrode gel solutions obtained in Comparative Examples and Example 5

[0099]

[0100] Referring to Table 5, there was no significant difference in the internal resistance and initial capacity of the lithium-ion batteries assembled using the two schemes, indicating that the addition of the surface tension leveling agent has virtually no impact on the internal resistance and capacity of the lithium-ion batteries. Furthermore, the capacity retention rate of the comparative example after 400 cycles was slightly higher than that of Example 5, but there was a sharp drop from the cycle retention rate of 200 cycles to the cycle retention rate of 400 cycles. Conversely, while the cycle performance of the examples was not particularly high, it remained relatively stable. In battery pack applications, the results reflected in Example 5 represent higher consistency and are more likely to be accepted by the market.

[0101] Based on this, combine Figure 5 and Figure 6 It can be seen that the coating state of Example 5 is better than that of the comparative example, because the comparative example is prone to edge lifting during coating, and in severe cases, even cracks appear. The electrode sheet qualification rate is lower than that of Example 5.

[0102] This application provides a method for preparing a negative electrode colloidal solution that facilitates the full and uniform dispersion of binders and negative electrode active materials, reducing agglomeration. It also promotes the thorough coating of the negative electrode active material by the conductive agent, thereby improving the surface condition of the negative electrode sheet. This surface tension leveling agent improves the self-leveling effect of the negative electrode colloidal solution and prevents binder chains from breaking due to high-speed stirring, enhancing the suspending effect of the binder and thus positively impacting the stability of the negative electrode colloidal solution. Simultaneously, it reduces the difficulty of coating the negative electrode colloidal solution. During the drying process of the negative electrode sheet, the uniform distribution of the negative electrode active material within the metal foil eliminates the defective phenomenon of electrode edge curling, providing stability assurance for subsequent processes such as lithium battery assembly and improving the finished product qualification rate of lithium batteries. Furthermore, it also has a wetting effect, facilitating the rapid and uniform mixing of raw materials to form a negative electrode colloidal solution, shortening the stirring preparation time, and improving production efficiency.

[0103] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention, but such modifications or substitutions are all within the scope of protection of the present invention.

Claims

1. A negative electrode colloidal liquid, characterized in that: The anode material includes, by mass, 3500 parts of anode active material and 36-60 parts of surface tension leveling agent, wherein the surface tension leveling agent is isopropanol, ethylene carbonate and polyether dimethylfluorosiloxane. The preparation method of the negative electrode colloidal solution is as follows: Step 1: Prepare the surface tension leveling agent. Prepare an aqueous solution of polyether dimethyl fluorosiloxane and an aqueous solution of ethylene carbonate. Add the prepared aqueous solution of ethylene carbonate to the prepared aqueous solution of polyether dimethyl fluorosiloxane to adjust the polarity. Finally, add isopropanol to the solution to prepare the surface tension leveling agent and set it aside for later use. Step 2: Mix the negative electrode active material, conductive agent, and binder evenly, add deionized water to break up the powdered material into large clumps, increase the stirring speed, gradually add deionized water until the solid content is adjusted to 52%±0.5%, stir at room temperature, then add surface tension leveling agent and emulsifying regulator, add deionized water to adjust the viscosity to 2000-3000 cP, vacuum and keep for at least 40 minutes to defoam, filter to obtain the negative electrode colloidal liquid.

2. The negative electrode colloidal liquid according to claim 1, characterized in that: It includes 0-65 parts isopropanol, 0-36 parts ethylene carbonate, and 0-40 parts polyether dimethyl fluorosiloxane, wherein none of the three substances are 0 parts.

3. The negative electrode colloidal liquid according to claim 1 or 2, characterized in that: The negative electrode colloidal solution comprises 35 parts conductive agent, 39.4 parts binder and 145.9 parts emulsifier.

4. The negative electrode colloidal liquid according to claim 3, characterized in that, The negative electrode active material is one or both of natural graphite and artificially synthesized graphite; The conductive agent is at least one of carbon black and conductive graphite; The emulsifying modifier is polystyrene-butadiene rubber; The adhesive is at least one of sodium carboxymethyl cellulose and synthetic lithium carboxymethyl cellulose.

5. A negative electrode sheet, characterized in that, The negative electrode gel liquid according to any one of claims 1-4 is coated on copper foil, and the negative electrode sheet is obtained after drying, rolling and cutting.

6. A lithium-ion battery, characterized in that, It includes a positive electrode, a separator, an electrolyte, a battery cap, and the negative electrode as described in claim 5.

Citation Information

Patent Citations

  • Negative electrode glue solution as well as preparation method and application thereof

    CN114335528A

  • Negative electrode slurry of lithium ion battery, preparation method of negative electrode plate and negative electrode plate

    CN116190651A

  • Negative plate, preparation method thereof and lithium battery

    CN118367103A

  • Negative electrode slurry and preparation method thereof, negative electrode plate and lithium ion battery

    CN119297282A